International agency implementation of women's empowerment programs under secular and Islamist governments: comparative cases of UN Women and the International Labour Organization experiences in Egypt - Buchanan, Whitney (AUC Knowledge Fountain, 2015)
This research compares two international agencies, the UN Women (UNW) and the International Labour Organization (ILO), and their women’s empowerment programs specifically under the Mubarak government during 2010 and under the Morsi government during 2012 to determine how Islamist and secular government support shapes the effectiveness of international agencies’ gender empowerment projects. This project is a “snapshot” of attitudes of particular ILO and UNW staff members from regional and national offices regarding their work during two different time frames, and not the institutional policies, experiences, or positions of he UNW and ILO bodies as a whole. The principal investigator chose to focus on elements concerning authoritarian and Islamist administrations, as well as the transition possibilities between them, because there is a gap in literature concerning how these types of governments could holistically affect international agencies women’s empowerment programs, and in turn, impact gender equality outcomes. As governmental changes have drastic social, economic and political impacts on civil society, government support for international agencies’ programs concerning gender development and women’s empowerment may shift when there is a transition between a secular government, and an Islamist government. Case studies were completed of six projects implemented by the two agencies that extended from the Mubarak 2010 through the Morsi 2012 administration. The principal investigator used in-depth online and in-person surveys, as well as interviews with ILO and UNW staff members. Key findings show that the Morsi era was more disruptive to agency programming on a higher level and that there was a change in government support for the UNW and ILO women’s empowerment programs between the two periods studied. In general, the exploratory study found that the change in environment, specifically during Morsi’s presidency, led to alterations in the workplace and women’s programs, which were deemed negative in nature for both the ILO and UNW employees. Findings strongly support that the projects, in regards to capacity building, implementation, and other elements, were viewed as more successful during the Mubarak 2010 administration. The findings also demonstrate the need to contemplate how changes of government can potentially affect programs when underlying values are challenged.